Experimental platform for the investigation of magnetized-reverse-shock dynamics in the context of POLAR. (16th July 2018) - Albertazzi, B.; Falize, E.; Pelka, A.; Brack, F.; Kroll, F.; Yurchak, R.; Brambrink, E.; Mabey, P.; Ozaki, N.; Pikuz, S.; Van Box Som, L.; Bonnet-Bidaud, J. M.; et al.
Abstract : The influence of a strong external magnetic field on the collimation of a high Mach number plasma flow and its collision with a solid obstacle is investigated experimentally and numerically. The laser irradiation ( I2× 10^14 W· cm^-2 ) of a multilayer target generates a shock wave that produces a rear side plasma expanding flow. Immersed in a homogeneous 10 T external magnetic field, this plasma flow propagates in vacuum and impacts an obstacle located a few mm from the main target. A reverse shock is then formed with typical velocities of the order of 15–20 ± 5 km/s. The experimental results are compared with 2D radiative magnetohydrodynamic simulations using the FLASH code. This platform allows investigating the dynamics of reverse shock, mimicking the processes occurring in a cataclysmic variable of polar type.